Handbook on jurisdiction of the Securities and Exchange Commission and other intra-corporate cases - Balbastro, Arturo E. (Manila Rex Book Store, 1992)
Contents: Basic principles and concepts. Selected Supreme Court decisions. Cases where SEC has jurisdiction. Cases where regular courts have jurisdiction. Cases where NLRC has jurisdiction. It is bound to clarify the jurisdictional boundaries and statutory provisions of the Securities and Exchange Commission in relation to the regular courts and the National Labor Relations Commission according to the Supreme Court.
Contents: "Pertinent statutory provisions and applicable jurisprudence on the jurisdiction and provisional powers of the securities and exchange commission."
Purpose: "To help shed light on problems arising from such gray areas, identify the jurisdictional boundaries, and formulate guidelines in this rather new and highly specialized field of law practice."
Keywords: Securities -- Philippines -- Handbooks, manuals, etc